2017
DOI: 10.3892/etm.2017.4289
|View full text |Cite
|
Sign up to set email alerts
|

Medical perspective in testicular ischemia-reperfusion injury

Abstract: Abstract. Testicular torsion or torsion of the spermatic cord is one of the most serious urological conditions. It causes testicular injury, which potentially leads to male subfertility. The turning of the spermatic cord and spermatic structures around themselves results in biochemical and histological changes; however, following testicular detorsion, tissues undergo reperfusion that causes more severe damage than that induced by ischemia. Since the primary causes of testicular damage are reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 108 publications
(112 reference statements)
0
29
0
Order By: Relevance
“…The testicular injury was thought to be a result of both the ischaemia and the reperfusion. However, the elaboration of free radicals during the period of reperfusion revealed to be the basis of pathogenesis of the injury (Arena et al, 2017; Asadi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The testicular injury was thought to be a result of both the ischaemia and the reperfusion. However, the elaboration of free radicals during the period of reperfusion revealed to be the basis of pathogenesis of the injury (Arena et al, 2017; Asadi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Ischaemia deprives the organ of its blood supply causing accumulation of waste products, while reperfusion results in elaboration of reactive oxygen species (ROS) and accumulation of calcium load in the testicular tissue. As a consequence, the oxidative stress and the inflammatory process are initiated (Arena et al, 2017). Deprivation of oxygen mainly affects the spermatogenesis, the most active replicative process with high degrees of mitochondrial oxygen consumption (Aitken & Roman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified reperfusion as the major cause of tissue damage (Ünsal et al, 2006). Because the main reasons of testicular injury are the overproduction of reactive oxygen species, calcium accumulation inside mitochondria and increased cellular apoptosis, various drugs can be useful (Arena et al, 2017). Recent studies have demonstrated that reperfusion can cause a noticeable increment in the overgeneration of lipid peroxidation, nitric oxide and germ cell apoptosis (Yuluğ et al, 2014).…”
Section: Testicular Ischaemia Reperfusion Caused By Torsion Detorsionmentioning
confidence: 99%
“…Calcium channel blockers are a group of medications that prevent Ca 2+ entrance to sensitive cells (Katz, 1986). Also, a lot of drugs in this group, like amlodipine, nifedipine, verapamil and lidocaine, have antioxidant properties (Arena et al, 2017). Sarica et al (1999) reduce the I/R damage and the sperm parameters assessment in various groups indicated that verapamil cannot remarkably meliorate the sperm characteristics; it is perhaps based on verapamil calcium channel-blocking activity that perhaps blocked the Ca2+/Na+ channels of spermatozoa and could not increase the motility and percentage of normal spermatozoa (Ameli et al, 2018).…”
Section: Deepa Et Al In Research On the Impacts Of Heparin On Cell Pmentioning
confidence: 99%
“…4,5 Such conditions can cause structural and functional loss of testicular tissue, which leads to the disruption of the spermatogenesis process, thus causing infertility. [5][6][7] Malondialdehyde (MDA) is an organic compound formed from ROS with the formula of CH2(CHO)2. Hence, MDA is used as an oxidative stress biomarker during ischemia and ischemia-reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%